How Far Will an Islamic Bank with The Largest Asset Elevate? - Masruri Muchtar (Faculty of Economic and Business, 2021)
Indonesian Islamic banking continues to show positive developments. Banking assets, the amount of financing, and third party funds continues to grow. A critical question arises particularly related to the issue of efficiency and effectiveness. This study is aimed to assess the level of efficiency of Bank of Shariah Mandiri (BSM) as an Islamic bank with the largest asset and to analyze factors that affect its level of profitability over the period of 2001-2019. Data Envelope Analysis was employed to assess efficiency and ordinary least square regression was applied for profitability analysis. The results show that the level of efficiency of BSM is categorized high with an average efficiency score of 97.7% but with the average level of profitability of only 1.3%, which is considered as medium. The level of efficiency was at the lowest point in 2003. Non-Performing Financing (NPF), Financing to Deposits Ratio (FDR), Operational Cost to Operational Income (BOPO), and Capital Adequacy Ratio (CAR) simultaneously have a significant effect on the level of profitability, but independently, FDR does not. The results imply that an Islamic bank with a gigantic asset shall give attention to its profitability while maintaining efficiency level.Cara Mengutip:Muchtar, M. (2021). How Far Will an Islamic Bank With The Largest Asset Elevate? Esensi: Jurnal Bisnis dan Manajemen, 11(1), xx-xx. https://doi.org/10.15408/ess.v11i1.20393.